Poverty, household food security, and nutrition in rural Pakistan - Alderman, Harold; Garcia, Marito (International Food Policy Research Institute, 1993)
The pathways from economic and social policies to improved food security and nutrition for the poor often are not well understood. Yet each day governments decide on policies that ultimately affect their well-being. How households increase their incomes, acquire food, improve health, or cope with insecurity are important concerns that need to be examined in order to devise policies to help eradicate poverty. Nearly all attempts to study these issues have used snapshot approaches--those that look at one point in time. These approaches are limited in that they do not reveal anything about the actual dynamics of poverty, food security, and their consequences for nutrition and health. In this report Harold Alderman and Marito Garcia address these concerns by looking at longitudinal data for a three-year period, 1986-89, and analyzing fluctuations in incomes, consumption, savings, nutrition and health-seeking behavior of 800 households in five districts in rural Pakistan (Faisalabad and Attock in Punjab province, Badin in Sind, Dir in North-West Frontier Province, and Mastung/Kalat in Baluchistan). The report examines income sources and wage formation in rural Pakistan and investigates the level and distribution of income in poor households. It contributes to analysis of the temporal dimensions of poverty and thus adds to the literature on coping strategies of households. Although the three-year panel of data analyzed is too short to model fully the dynamics of poverty, it is sufficient to indicate the fluidity of the economic environment that households in Pakistan face. The report also traces the efficiency by which household incomes are converted to better nutritional well-being and the influence of other intervening factors such as health and education.